Recovery-stress balance and injury risk in professional football players: a prospective study - Laux, P.; Krumm, B.; Diers, M.; Flor, H. (Journal of Sports Sciences, 2015)
Professional football is a contact sport with a high risk of injury. This study was designed to examine the contribution of stress and recovery variables as assessed with the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport) to the risk of injury in professional football players. In a prospective, non-experimental cohort design, 22 professional football players in the highest German football league were observed over the course of 16 months. From January 2010 until April 2011, the players completed the RESTQ-Sport a total of 222 times in monthly intervals. In addition, injury data were assessed by the medical staff of the club. Overall, 34 traumatic injuries and 10 overuse injuries occurred. Most of the injuries were located in the lower limb (79.5%), and muscle and tendon injuries (43.2%) were the most frequently occurring injury type. In a generalised linear model, the stress-related scales Fatigue (OR 1.70, P = 0.007), Disturbed Breaks (OR 1.84, P = 0.047) and Injury (OR 1.77, P < 0.001) and the recovery-related scale Sleep Quality (OR 0.53, P = 0.010) significantly predicted injuries in the month after the assessment. These results support the importance of frequent monitoring of recovery and stress parameters to lower the risk of injuries in professional football.